Genome-wide analysis of abdominal and pleural malignant mesothelioma with DNA arrays reveals both common and distinct regions of copy number alteration. Issue 3 (3rd March 2016) - Borczuk, Alain C.; Pei, Jianming; Taub, Robert N.; Levy, Brynn; Nahum, Odelia; Chen, Jinli; Chen, Katherine; Testa, Joseph R.
ABSTRACT: Malignant mesothelioma (MM) is an aggressive tumor arising from mesothelial linings of the serosal cavities. Pleural space is the most common site, accounting for about 80% of cases, while peritoneum makes up the majority of the remaining 20%. While histologically similar, tumors from these sites are epidemiologically and clinically distinct and their attribution to asbestos exposure differs. We compared DNA array-based findings from 48 epithelioid peritoneal MMs and 41 epithelioid pleural MMs to identify similarities and differences in copy number alterations (CNAs). Losses in 3p ( BAP1 gene), 9p ( CDKN2A ) and 22q ( NF2 ) were seen in tumors from both tumor sites, although CDKN2A and NF2 losses were seen at a higher rate in pleural disease (p<0.01). Overall, regions of copy number gain were more common in peritoneal MM, whereas losses were more common in pleural MM, with regions of loss containing known tumor suppressor genes and regions of gain encompassing genes encoding receptor tyrosine kinase pathway members. Cases with known asbestos causation (n = 32 ) were compared with those linked to radiation exposure (n = 9 ). Deletions in 6q, 14q, 17p and 22q, and gain of 17q were seen in asbestos-associated but not radiation-related cases. As reported in post-radiation sarcoma, gains outnumbered losses in radiation-associated MM. The patterns of genomic imbalances suggest overlapping and distinct molecular pathways in MM of the pleura and peritoneum, and that differences in causation (i.e., asbestos vs. radiation) may account for some of these site-dependent differences